Genetic markers for inherited thrombophilia are associated with fetal growth retardation in the population of Central Russia. Issue 7 (19th May 2017) - Reshetnikov, Evgeny; Zarudskaya, Oksana; Polonikov, Alexey; Bushueva, Olga; Orlova, Valentina; Krikun, Evgeny; Dvornyk, Volodymyr; Churnosov, Mikhail
Abstract: Aim: The aim of this study was to examine the role of hereditary thrombophilia in the development of fetal growth retardation (FGR) in the population of Central Russia. Methods: The case–control study sample included 497 women in the third trimester of pregnancy recruited during 2009–2013. The participants were enrolled into two groups: patients with FGR ( n = 250) and controls without FGR ( n = 247). The participants were genotyped for four genetic markers of hereditary thrombophilia: factor V Leiden ( G > A FV, rs6025), prothrombin ( G > A FII, rs1799963), factor VII ( G > A FVII, rs6046), and fibrinogen ( G > A FI, rs1800790). Results: The genetic factors for an increased risk of FGR were allele G of rs6046 (odds ratio [OR] = 2.34) and genotype GG of rs6046 (OR = 2.64), whereas genotype GA of rs6046 had the protective value (OR = 0.42). A combination of alleles G of rs1799963, A of rs6046, and G of rs1800790 (OR = 0.31) reduces the risk of FGR. Conclusion: Polymorphism rs6046 of the FVII gene is associated with the development of FGR.